ALQURAN DAN PERADABAN MANUSIA: Perspektif Pendidikan Keseimbangan Duniawi dan Ukhrawi - M. Shabir U. (Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2007)
Human being is not perfect creature. He has a lot limitation and some needs in his life. In full feel his need, man creates civilization is becoming more and more progressive. In creating civilization causes of full feel his need. Human being is guided by almighty God through Alquran. Therefore, the man gets civilization must implicate the balance between world and hereafter.